2005
DOI: 10.1097/01.hjh.0000173778.85233.1b
|View full text |Cite
|
Sign up to set email alerts
|

Vascular methylglyoxal metabolism and the development of hypertension

Abstract: Increased aortic MG, AGE formation and oxidative stress were associated with blood pressure increase in SHR, which may cause endothelial dysfunction and altered vascular reactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
99
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(103 citation statements)
references
References 24 publications
(41 reference statements)
3
99
0
1
Order By: Relevance
“…In our study, the postprandial circulating MG levels increased maximally at 4 h, an effect prevented by benfotiamine. Dicarbonyls can induce oxidative stress, promote inflammation (42), and induce endothelial apoptosis (43) and dysfunction (44).…”
Section: Correlationsmentioning
confidence: 99%
“…In our study, the postprandial circulating MG levels increased maximally at 4 h, an effect prevented by benfotiamine. Dicarbonyls can induce oxidative stress, promote inflammation (42), and induce endothelial apoptosis (43) and dysfunction (44).…”
Section: Correlationsmentioning
confidence: 99%
“…18 In any case, it is well established that oxidative stress is associated with arterial blood pressure increase, which may cause endothelial dysfunction and altered vascular reactivity. 19 According to this view, it is conceivable that a drug able to decrease IOP could also have a protective action on endothelial cells.…”
mentioning
confidence: 99%
“…MG has been postulated to play a role in the development of hypertension [36]. Studies using animal model and cell cultures showed a significant increase in blood pressure to coincide with elevated MG level in plasma and aortic tissues [37], [38]. However, functional links between MG biogenesis and hypertension, in part mediated by ROS and AGEs, have only been documented in rat model but not yet in humans under these conditions.…”
Section: Resultsmentioning
confidence: 99%